2022
DOI: 10.3389/fsufs.2022.986655
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield improvement in high-quality rice varieties released in southern China from 2007 to 2017

Abstract: In recent years, high-quality rice varieties have been widely cultivated for food production in southern China. However, changes in the yield performance of different high-quality rice varieties are still unclear. In this study, the yield and yield components of 710 different types (hybrid or inbred rice and japonica or indica) of high-quality rice varieties were investigated in six provinces from 2007 to 2017. The results showed that, from 2007 to 2017, the grain yield and yield traits, including the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Therefore, attention should be paid to improving the spikelet number per panicle in early indica rice breeding. Meanwhile, we did not observe any correlation between grain yield and 1000-grain weight, which was consistent with previous findings that grain yield was independent of grain weight in indica rice [15,22]. These results suggest that, during indica rice breeding, the contribution of grain weight to yield improvement may be negligible.…”
Section: Grain Yield But Not Quality Was Improved During Early Indica...supporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, attention should be paid to improving the spikelet number per panicle in early indica rice breeding. Meanwhile, we did not observe any correlation between grain yield and 1000-grain weight, which was consistent with previous findings that grain yield was independent of grain weight in indica rice [15,22]. These results suggest that, during indica rice breeding, the contribution of grain weight to yield improvement may be negligible.…”
Section: Grain Yield But Not Quality Was Improved During Early Indica...supporting
confidence: 92%
“…Wang et al [22] analyzed the relationships between yield components and grain quality traits among different high-quality rice varieties, and they found that grain yield was positively correlated with the chalky rice rate, which was consistent with the results of this study (Figure 2). However, Wang et al [22], did not investigate relationships among grain quality traits, which are expected to hinder the collaborative improvement of grain quality traits. The results of this study indicate that a network of grain quality traits should be established to achieve the simultaneous improvement of multiple traits.…”
Section: Grain Yield But Not Quality Was Improved During Early Indica...supporting
confidence: 88%
See 3 more Smart Citations